Effects of sevoflurane and propofol on hemodynamics during cardiac surgery: A randomized controlled clinical trial - Bekzat Baiterek; Alibek Mustafin (National Scientific Medical Center, 2023)
The anaesthetic support for various types of cardiac surgery such as coronary artery bypass grafting, heart valve repair or replacement is essential for success of a surgery. The planning of anaesthesia depends on the intended surgical procedure. The traditional approach is total intravenous anesthesia with propofol and inhalation with sevoflurane. Objectives: To identify the advantages and disadvantages of propofol and sevoflurane when cardiac surgery in adults.   Material and methods: A total of 40 patients were assigned randomly into two groups to receive: in Group 1 - propofol and in Group 2 - sevoflurane. The induction to general anesthesia started with intravenous fractional administration of 1-1.5 mg/kg propofol, 5-7 µg/kg fentanyl and 1.5-2 mg/kg ketamine. Pipecuronium bromide 0.07-0.1 mg/kg was used as a myorelaxant in all patients in both groups. The anaesthesia in group P was supported with propofol 4-6 mg/kg/min intravenously by means of a perfusor as anaesthetic. In group 2, sevoflurane at a dose of 1.7-1.9 MAC was used as an anaesthetic. To maintain anaesthesia in both groups, there was a fractional administration of fentanyl at a dose of 100 µg intravenously when the heart rate and blood pressure increase, piperonium bromide in a dose of 2 mg intravenously was used for muscle relaxation. Results: The mean arterial pressure, oxygen demand, energy expenditure, cardiac index, total peripheral resistance showed statistically significant differences between propofol and sevoflurane groups. Through the correlation analysis, the relationship between cardiac index and oxygen consumption was moderately relevant, as R was 0.4 and P>0.05. Conclusion: When the use of sevoflurane for anesthesia, the hemodynamic parameters were stable. The oxygen consumption, energy expenditure in patients were significantly lower compared to propofol using the sevoflurane anesthesia.